Properties of high strength concrete containing spent garnet as sand - Budiea, Ahmed Mokhtar Albshir; N. N.M., Azhar; Shahrul Niza, Mokhatar; Khairunisa, Muthusamy; Mohd Khairul Idham, Satar (Institute of Physics, 2023)
Spent garnet is a waste resulting from abrasive media known as garnet and disposed into the landfill which can become threat to the environment. Meanwhile, the step of substituting sand by spent garnet can reduce sand exploitation activities which have been ongoing to fulfil the continuous development and construction. This work attempts to investigate the mechanical properties of specimens made of concrete that contains spent garnet. This new material replaces sand partially at different percentages of 10% and 20% by weight. The compressive strength test as well as splitting tensile test have been both conducted after 7 days and 28 days water curing. The results show an improvement of the strength during the compressive test. The increment appears to be in positive relationship with the replacement percentage. Meanwhile, splitting tensile strength testing shows that 20% performs better than 10% sand replacement. In conclusion, the inclusion of spent garnet in reasonable amount to take place instead of sand has improved the concrete's properties.